Jokowi's Agrarian Politics in the Agrarian Reform Program - Budhyatma, Erlangga Hikmah (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Maritim Raja Ali Haji, 2025)
This research is intended to see how Jokowi's agrarian politics is in the agrarian reform program. Indonesia is a country with a very high level of inequality in land tenure. By using a qualitative descriptive research approach, this research takes data from online media, the Institute's website, stakeholder statements, and government documents. The results of this study indicate that the majority of land ownership in Indonesia, which is less than 2 hectares, is 50,508,676 parcels with a total land area of 9,921,994.28 hectares. Meanwhile, land ownership is more than 20 hectares, which is only 4,878 parcels with a land area of 4,508,366.46. If using the world bank criteria, the inequality value in the 6 main islands in Indonesia is at a high inequality value because it is at < 12% of the value of the inequality. Meanwhile, with the implementation of the agrarian reform program from 2015-to 2020, the Jokowi government is only able to distribute 1.46 million hectares of land. This study concludes that the Jokowi government's agrarian politics is the same as the feudalism-style land tenure pattern which relies on land monopoly control.